Rebuilding wellbeing: Understanding the role of self-criticism, anger rumination, and death distress after the February 6, 2023, Turkiye Earthquake - Birni, Gaye; Deniz, M. Engin; Karaagac, Zahide Guel; Erisen, Yavuz; Kaya, Yagmur; Satici, Seydi Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This study investigated self-criticism, anger rumination, and death distress in wellbeing after one of the most devastating natural disasters of this century. The study included 399 participants from 56 different cities across Turkiye. Participants were from 3 groups: those who themselves or one of their nuclear families are earthquake survivors (group 1), those who had a loved one other than a nuclear family member who was an earthquake survivor (group 2), and those who were deeply affected by the earthquake through media networks (group 3). Results showed that women experienced higher death distress and anger rumination and lower mental wellbeing compared to men post-earthquake. Individuals in group 1 had significantly lower mental wellbeing and higher death distress than groups 2 and 3. However, the effect size of this significant differentiation depending on earthquake experience was small. Moreover, anger rumination and death distress fully mediated the link between self-criticism and mental wellbeing.
Keywords: POSTTRAUMATIC-STRESS-DISORDER; QUALITY-OF-LIFE; MENTAL-HEALTH; PSYCHOLOGICAL TRAUMA; MEDIATING ROLE; SURVIVORS; DEPRESSION; POPULATION; VICTIMS; BLAME; Psychology; Social Issues; Biomedical Social Sciences